Assessment of Nutritional Status of Pregnant Adolescents in Baghdad City - salih, Shaker; Abdul-Wahid, hala (Iraqi National Journal of Nursing Specialties, 2012)
Objectives: The study aims to assess the nutritional status, identify nutrition-related health problems andfind out the relationships between nutritional status and demographic characteristics of the pregnantadolescents in Baghdad City.Methodology: A descriptive study was carried out from April/20/2009 to June/30/2009 through a "Nonprobability"purposive sample of (196) pregnant adolescents their age between (13–19) years who attend (14)primary health care centers in Baghdad City seeking for antenatal care. The data were collected by theinvestigator who interviewed the pregnant adolescents and filled out the constructed questionnaire formatswhich designed for the purpose of the study. Internal consistency of reliability determined through thecomputation of alpha-Chronbach correlation coefficient for quality of life items. Test-retest of reliability wasdetermined through the computation of Spearman's correlation coefficient for the same items. The contentvalidity of the constructed questionnaire was determined through a panel of experts. Data were analyzedthrough the application of descriptive statistical approach (frequencies and percentages) and inferentialstatistical approach (Chi-Square).Results: The findings revealed that imparity in weight per (kg) according to the pregnancy trimester recordedthe following mean values (after excluding the extreme values). 1st trimester (0.00 – 0.66kg), 2nd trimester(2.83 – 3.51kg) and 3rd trimester (4.90 – 6.96kg). Regarding nutritional related problems; anemia,hypoglycemia, hyperglycemia, protein urea (trace), teeth decay and urinary tract infection, nausea, vomiting,and heartburn. Common dietary patterns: skipping meals, snacks eating, food dislike, and not drinking enoughamounts of water or beverages daily(6–8) glasses, The dietary intake through the (24) hours diet recall andfood frequency questionnaire which in comparison with food pyramid do not meet daily requirements of theirservings.Recommendations: The study recommends health promotion and nutrition-oriented education programscan be designed, structured and presented to female adolescents to prepare them for a healthy marriage andpregnancy.